Tomografia por biosusceptometria de corrente alternada - Fonseca Filho, Paulo Roberto da [UNESP] (2014)
The development of new imaging methods, especially those that are free of ionizing radiation, constitute a very important topic because for both instrumentation development and its applications. The Alternating Current Biosusceptometry (ACB) has versatility, sensibility and low cost and has been widely used on image acquisition on gastroenterology, physiology, pharmaceutics and pharmacology researches. The aim of this project was to characterize ACB systems to produce tomographic images of simulating objects ver-ifying the technical viability of the AC Biosusceptometry Tomography (ACBT). The capability of ACB gradiometers of 13 and 37 channel systems with compensation field to reconstruct images of bars and cy-lindrical phantoms were evaluated, especially sensibility and resolution. It was possible to reconstruct im-ages from all objects with good correlation between the image and the phantom (geometry and magnetic tracer concentration). Better results were observed while using multichannel acquisition on 37-channel sys-tem with active excitation magnetic field. Therefore we verified that ACB systems can be successfully used on tomographic imaging of objects with small quantities of magnetic tracer, which is viable to future ap-plication on small animal physiology, pharmaceutics or non-destructive evaluation research